PENGARUH KUALITAS PELAYANAN DAN DISIPLIN KERJA TERHADAP KEPUASAN MASYARAKAT PADA KANTOR LURAH KLENDER JAKARTA TIMUR - eulin karlina; Oki Rosanto; Nur Eka Saputra (Universitas Bina Sarana Informatika, 2019)
Abstract - In the organization of good service of efficient and efficient activities. The better the service will affect the level of satisfaction felt by the community. These efforts will increase higher. Enforcement of discipline makes work more effective and efficient. The research method used is descriptive quantitative by digging data using techniques, interviews and questionnaires. Test the instrument using Product Moment's expression and reliability test using Alpha Cronbach's. Hypothesis test consists of simple regression test and multiple regression test. The results showed that: (1) there was a positive relationship between Quality of Service to Satisfaction Society with rx1y = 0,594; r2x1y = 0.353; t count (8,196)> t table (1,979) at 5% significance level. (2) positive condition between Work Discipline to Satisfaction of Society with rx2y = 0,59; r2x2y = 0.359; t arithmetic (8.298)> t table (1.979) at a significance level of 5%. (3). Conditions and Discipline Against Satisfaction of Society with Ry(1,2) = (0,671); R2y (1,2) = (0,450) F value count (49,989)> F table (3,07) at 5% significance level. Keywords: Service Quality, Work Discipline, Public Satisfaction.